Flies (Insecta, Diptera) collected in the environment of dairy farms as carriers of Rotavirus A and betacoronavirus - Bertolini, Amanda Bezerra [UNESP]; Thyssen, Patrícia Jacqueline; Brandão, Paulo Eduardo; Prado, Aline Marrara; Silva, Sheila Oliveira de Souza; Mioni, Mateus de Souza Ribeiro [UNESP]; de Gouvea, Fábio Lucas Rezende [UNESP]; Pantoja, José Carlos de Figueiredo [UNESP]; Langoni, Helio [UNESP]; Guimarães, Felipe Freitas [UNESP]; Joaquim, Sâmea Fernandes [UNESP]; Guerra, Simony Trevizan [UNESP]; et al. (Oxford University Press (OUP), 2023)
AIMS: We aimed to investigate the prevalence of rotavirus and coronavirus in dipterans that commonly inhabit the environment of dairy farms. METHODS AND RESULTS: We collected 217 insect specimens from nine dairy farms, which were examined through hemi-nested RT-PCR followed by Sanger sequencing in search of VP1 and N genes for rotavirus and bovine coronavirus-BCoV, respectively. With a predominance of Muscidae (152/217 = 70%) 11 families of Diptera were identified. Rotavirus A (RVA) and betacoronavirus (BCoV) were detected in 14.7% (32/217) and 4.6% (10/217) of the dipterans, respectively. Sequencing of the amplicons was possible for 11.5% (25/217) of RVA and 0.5% (1/217) of BCoV, confirming the presence of these pathogens. CONCLUSIONS: Our findings highlight the role of dipterans as carriers of RVA and BCoV of great relevance for public and animal health.
Keywords: BCoV; dairy cows; flying insects; RVA; Vector-borne diseases